A matter of sex—persistent predictive value of MECKI score prognostic power in men and women with heart failure and reduced ejection fraction: a multicenter study - Grilli, Giulia; Salvioni, Elisabetta; Moscucci, Federica; Bonomi, Alice; Sinagra, Gianfranco; Schaeffer, Michele; Campodonico, Jeness; Mapelli, Massimo; Rossi, Maddalena; Carriere, Cosimo; Emdin, Michele; Piepoli, Massimo; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: A sex-based evaluation of prognosis in heart failure (HF) is lacking.We analyzed the MECKI score registry which includes HF with reduced ejection fraction (HFrEF) patients. A cross-validation procedure was performed to estimate weights separately for males and females of all MECKI score parameters: left ventricular ejection fraction (LVEF), hemoglobin, kidney function assessed by MDRD, blood sodium level, ventilation vs. carbon dioxide production slope, and peak oxygen consumption (peakVO2). The primary outcomes were the composite of all-cause mortality, urgent heart transplant and LVAD implant. The difference in predictive ability between the native and sex re-calibrated MECKI (S-MECKI) was calculated with the ROC curve at 2-years and a calibration plot.We retrospectively analyzed 7900 HFrEF patients included in the MECKI score registry (61±13 years, 6456 M/ 1444 F, LVEF 33±10 %, peakVO2 56.2±17.6 % of predicted) with a median follow up of 4.05 years [1.72-7.47]. Our results revealed an unadjusted risk of events doubled in males compared to females (9.7 vs. 4.1) and a significant difference in weight between sexes of most of the parameters included in the MECKI score. S-MECKI showed improved risk classification and accuracy (AUC 0.7893 vs. 0.7799, p=0.02 due to prognostication improvement in the high-risk settings in both sexes (MECKI score >10 in males and >5 in females).Conclusions: S-MECKI, i.e. the re-calibrated MECKI according to sex-specific differences, constitutes a further step in the prognostic assessment of patients with severe HFrEF.